Effectiveness of Mindfulness-Based Cognitive Therapy on Anxiety and Self-Care in Patients with Hypertension - Mahmoodian, Bita; Rastegar Kuchaksaraei, Morvarid; Karami Alam, Fatemeh; Amirteimouri, Hadiyeh; Mohammadali Nasab, Shamim (Health Nexus, 2023)
The aim of this study was to determine the effectiveness of mindfulness-based cognitive therapy on anxiety and self-care in patients with hypertension. The research method was quasi-experimental, employing a pre-test and post-test design with a control group. The statistical population of this study consisted of patients with hypertension who visited health centers in Tehran during the three months of the winter season in the year 2022. From this population, 30 individuals were selected through convenience sampling and randomly assigned to two groups: an experimental group (15 people) and a control group (15 people). In this study, anxiety and self-care questionnaires were used. The experimental group received eight 2-hour sessions of mindfulness-based cognitive therapy, while the control group did not receive any specific intervention. The findings showed that anxiety and self-care scores in the post-test were reduced compared to the pre-test in the experimental group. Therefore, mindfulness-based cognitive therapy has an impact on anxiety and self-care in patients with hypertension.